1993
DOI: 10.1128/iai.61.8.3490-3495.1993
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the human antibody response to thrombospondin-related anonymous protein of Plasmodium falciparum

Abstract: Thrombospondin-related anonymous protein (TRAP) of the malaria parasite Plasmodiumfalciparum shares two sequence motifs with other proteins which possess adhesive properties. Recently, findings indicate that TRAP is an antigen which contributes to antisporozoite immunity. We have cloned and expressed the TRAP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…However, the difference between dry and wet seasons is markedly greater in the < 4-year-age class than among the 5-9-year-olds and the 10-19-year-age class. Similar patterns have been reported recently in region of West Africa where malaria is hyperendemic (Scarselli et al 1993). This implies that recovery rates are higher among those under 4 years of age, as the effect of a change in transmission will manifest itself as a change in parasite rates only if the duration of parasitaemia is short.…”
Section: Discussionsupporting
confidence: 86%
“…However, the difference between dry and wet seasons is markedly greater in the < 4-year-age class than among the 5-9-year-olds and the 10-19-year-age class. Similar patterns have been reported recently in region of West Africa where malaria is hyperendemic (Scarselli et al 1993). This implies that recovery rates are higher among those under 4 years of age, as the effect of a change in transmission will manifest itself as a change in parasite rates only if the duration of parasitaemia is short.…”
Section: Discussionsupporting
confidence: 86%
“…Previous work has shown that volunteers immunized with irradiated sporozoites (27) and West African adults and children (29) have antibodies to recombinant PfSSP2/TRAP. We found that residents of malaria-endemic areas had antibodies to the (DRYIPYSP) 3 and (CHPSDGKCN) 2 epitopes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, two extracellular portions of malarial TRAP, the von Willebrand A‐domain and the thrombospondin repeats located in domains II and IV, respectively, are crucial for initial host cell adherence and stabilisation of adhesion/deadhesion during gliding mobility of sporozoites . Importantly, naturally acquired antibodies against P. falciparum TRAP (PfTRAP) exhibited less parasite density among individuals in malaria hyperendemic areas, supporting the role of this molecule in eliciting protective immunity against malaria parasite . Furthermore, immunisation of Aotus monkeys with P. vivax TRAP (PvTRAP)‐derived peptide has conferred partial protection upon challenge infection with a heterologous parasite strain .…”
Section: Introductionmentioning
confidence: 96%